2017
DOI: 10.1186/s12866-017-0956-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial survey of ready-to-eat salad ingredients sold at retail reveals the occurrence and the persistence of Listeria monocytogenes Sequence Types 2 and 87 in pre-packed smoked salmon

Abstract: BackgroundAs the preparation of salads involves extensive handling and the use of uncooked ingredients, they are particularly vulnerable to microbial contamination. This study aimed to determine the microbial safety and quality of pre-packed salads and salad bar ingredients sold in Singapore, so as to identify public health risks that could arise from consuming salads and to determine areas for improvement in the management of food safety.ResultsThe most frequently encountered organism in pre-packed salad samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 52 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…This might be linked to the fact that people over 65 years of age, with high notification rates, are not expected consumers of this type of salads, and by that reason were not considered high‐risk population in the study. Additionally, even the number of cases of listeriosis attributed to high‐risk groups, especially immunocompromised patients, may be overestimated, since most of these patients are often advised to avoid the consumption of these types of products, exactly because of the potential health risk it represents (Chau et al., 2017; United States of America Centers for Disease Control and Prevention [USA‐CDC], 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This might be linked to the fact that people over 65 years of age, with high notification rates, are not expected consumers of this type of salads, and by that reason were not considered high‐risk population in the study. Additionally, even the number of cases of listeriosis attributed to high‐risk groups, especially immunocompromised patients, may be overestimated, since most of these patients are often advised to avoid the consumption of these types of products, exactly because of the potential health risk it represents (Chau et al., 2017; United States of America Centers for Disease Control and Prevention [USA‐CDC], 2018).…”
Section: Resultsmentioning
confidence: 99%
“…(47.6%, 10/21) and L. monocytogenes (2.0%, 6/303), whose psychrotrophic nature has posed a challenge to the fish industry. L. monocytogenes is also a concern in chilled RTE food because of its ubiquity and persistence in food-processing environments ( 25 ). …”
Section: Discussionmentioning
confidence: 99%
“…Although several studies reported that lineage II isolates were significantly overrepresented in foods [61][62][63][64][65][66][67], other studies reported that lineage I isolates predominate in foods. For example, Sauders et al [68] [35], 60% of a collection of 81 isolates from RTE meat products in processing plants and retail establishments in central Portugal sampled between 2011 and 2013 [70], and 82.8% of a collection of 64 food isolates from retail establishments and supermarkets in Singapore sampled between 2011 and 2012 [71].…”
Section: Comparison Of the Proportions Of Isolates By Lineage For Isomentioning
confidence: 99%